Ucinek vadbe za moc vdišnih mišic na šprintersko zmogljivost mladih plavalk in plavalcev - Kapus, J. (Kinesiologia Slovenica, 2013)
The purpose of this study was to investigate the effects of inspiratory muscle training (IMT) on inspiratory muscle strength and sprint swimming performance in young swimmers. Twelve healthy participants (seven females, five males; age: 14±1 years, height: 1.70±0.06 m, body mass: 58±9 kg) were divided into two groups: an experimental (Group E) and placebo IMT control (Group C). IMT was added to the usual daily swimming practice. It was performed twice daily for six weeks using a spring-loaded threshold inspiratory muscle trainer. Group E performed 30 dynamic inspiratory efforts against a pressure-threshold load of ~50% maximal inspiratory pressure. In contrast, Group C trained with a protocol involving 30 slowly protracted breaths against a pressure-threshold load of ~15% maximal inspiratory pressure. Participants completed the following tests in the same order in pre- and post-training: tests of pulmonary function, tests of respiratory muscle strength, and 50 m and 100 m swim time trials. After IMT, Group E showed higher inspiratory (+62 ± 42%; p=0.00) and expiratory muscle strength (+17 ±10%; p=0.00) and swam the 50 m butterfly (+2±2%; p=0.03) and the 100 m front crawl (+2±2%; p=0.04) faster. However, the times in other sprint swimming trials (50 m front crawl and 50 m breaststroke), stroking and breathing characteristics did not change throughout the IMT in Group E. As expected, these parameters were unchanged in Group C. In conclusion, the IMT increased respiratory muscle strength in the young swimmers. However, these improvements are only partially transferable to sprint swimming performance.